Pengaruh pelatihan kader jumantik dengan ovitrap terhadap peningkatan pengetahuan demam berdarah dengue (DBD) siswa SDN 33 Jollo dan SMP 5 Satap Bungoro, Kabupaten Pangkep tahun 2023 - Basir; Amir, Safrullah; Arsin, Andi Arsunan; Ridjal, Andi Tilka Muftiah; Andini; Rosadi, Andi Rifkah Kifayah; Azhar, Gadis Ariqah Fahriyani; Kurniawan, Nanang; Mar’a, Ni’matul; Darwis, Nurhaliza (EcoVision: Journal of Environmental Solutions, 2024)
Background: The service aims to reduce the incidence of dengue hemorrhagic fever (DHF) through basic training of Jumantik cadres using simple educational materials (Ovitrap) in Bungoro District, Pankep Regency. Methods: The target of this service consisted of students of Pangkep Regency, Bungoro District, precisely at SDN 33 Jollo and SMPN 5 SATAP Bungoro. The sample of this study consisted of students aged between 9 and 15 years and totaled 26 students. Findings: The results of this service were 3 participants (11.5%) who experienced an increase in knowledge from pre-test to post-test. In 23 participants (88.5%), there was no increase or decrease in pre-test and post-test scores. Even if knowledge increases, according to the Wilcoxon test, the p-value of 0.083 is greater than 0.05 so it can be concluded that Ha is rejected and H0 is accepted. Conclusion: There is no significant difference in improvement, pre-test and post-test knowledge can be classified as good, depending on the ability of students to apply Ovitrap production in the classroom.